2006
DOI: 10.1161/01.hyp.0000249511.96555.57
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Potassium Channels by Tempol in Arterial Smooth Muscle Cells From Normotensive and Deoxycorticosterone Acetate-Salt Hypertensive Rats

Abstract: Abstract-Large-conductance Ca 2ϩ -activated potassium (BK) channels modulate vascular tone. Tempol, an O 2 Ϫ dismutase mimetic, causes vasodilation via activation of vascular BK channels. In this study, we investigated the mechanisms underlying tempol-induced activation of BK channels in mesenteric arterial (MA) myocytes from sham and deoxycorticosterone acetate (DOCA)-salt hypertensive rats. In sham myocytes, whole-cell patch clamp studies showed that tempol enhanced peak outward currents (I o O2Ϫ is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Tempol directly activates vascular Ca 2+ -activated potassium channels, modulating the vascular smooth muscle tone. 40 We found that a discrete vasodilation was induced by direct injection of tempol in MABs only when very high doses of the antioxidant were used (data not shown). The improvement in ACh-induced vasodilatory effect observed in our study was a result of chronic treatment with tempol, given that the vascular preparation was perfused with PSS without addition of the antioxidant.…”
Section: Discussionmentioning
confidence: 85%
“…Tempol directly activates vascular Ca 2+ -activated potassium channels, modulating the vascular smooth muscle tone. 40 We found that a discrete vasodilation was induced by direct injection of tempol in MABs only when very high doses of the antioxidant were used (data not shown). The improvement in ACh-induced vasodilatory effect observed in our study was a result of chronic treatment with tempol, given that the vascular preparation was perfused with PSS without addition of the antioxidant.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that tempol is, in fact, sympathoinhibitory in hypertensive rats (17,24). A caveat to this conclusion, however, is that tempol also has other pharmacological effects [e.g., opening large conductance, calcium activated potassium channels (64)] and sites of action (e.g., blood vessels, kidney or brain) that could attenuate sympathetic activity and/or hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…While tempol has been widely used as a superoxide scavenger in physiological studies (11,19,48,55), this compound also possesses a property to open ATP-sensitive and Ca 2ϩ -activated K ϩ channels (7,52,53). Recently, tempol has been shown to suppress the exaggeration of the exercise pressor reflex in rats whose femoral artery had been ligated for 72 h independent of its antioxidant effects (32) but through its effect to open ATP-sensitive K ϩ channels (53).…”
Section: Methodsmentioning
confidence: 99%